Bioelectromechanical Properties of Alginate through Piezoresponse Force Microscopy: An Insight with a Computer Simulation with Free Radicals - Heredia-Barbero, A.; Gervacio-Arciniega, J. J.; Duarte-Alaniz, V.; Amelines-Sarria, O.; Rodríguez-Galván, A.; Siqueiros, J. M. (New Trends in Physical Science Research Vol. 7, 2022)
Piezoresponse force microscope imaging, scanning electron microscopy, powder X-rays, infrared spectroscopy, and computer simulations were used to investigate the alginate biopolymer from Tropicalgin C302245. In the out of plane mode, local piezoresponse force microscopy images reveal probable ferroelectric zones, which are validated by second harmonic generation analysis. Diatom frustules with a cristobalite-like substance, amorphous silica, and chitin make up alginate powder. The experimental results are explained by MM+ and PM3 computer simulations, which show that alginate molecule self-assembly increases the molecular collective dipole moment, enhancing polarization. Preliminary free radical calculations suggest less thermodynamic stability in alginate biopolymer decreasing hydrogen bonding thus, decreasing ferroelectric properties. Alginate molecular properties might open possibilities for organic green technological applications.